2023
DOI: 10.1186/s12610-023-00200-3
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanism of Shugan Yidan fang, a Chinese herbal formula, in rat model of premature ejaculation

Qiang Han,
Jun Guo,
Renyuan Wang
et al.

Abstract: Background Premature ejaculation (PE) is one of the most common forms of sexual dysfunction in men, and multimodal therapeutic regimens should be considered to treat the condition. We developed a Chinese medicine herbal medicine, Shugan Yidan fang that had a significant clinical effect on PE patients, extending the time between penetration and ejaculation. However, the mechanism of this formula remains unclear. There is evidence that PE is associated with peripheral neuropathology, and the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…[7] Han et al postulated that a formula to soothe the liver and benefit the gallbladder could improve behavioral characteristics in PE rats, reduce the expression of dopamine receptor messenger ribonucleic acid (mRNA) and protein, and simultaneously enhance the levels of dopamine transporter. [8]…”
Section: Tcm Characteristic Treatmentmentioning
confidence: 99%
“…[7] Han et al postulated that a formula to soothe the liver and benefit the gallbladder could improve behavioral characteristics in PE rats, reduce the expression of dopamine receptor messenger ribonucleic acid (mRNA) and protein, and simultaneously enhance the levels of dopamine transporter. [8]…”
Section: Tcm Characteristic Treatmentmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors reported an error in the title of the article. The original title “Mechanism of Shugan Yidan fan, a Chinese herbal formula, in rat model of premature ejaculation” should be replaced with “Mechanism of Shugan Yidan fang, a Chinese herbal formula, in rat model of premature ejaculation”.…”
mentioning
confidence: 99%